PERSPECTIVES ON THE USE OF TRICLOSAN-COATED SUTURES TO PREVENT SURGICAL SITE INFECTIONS - Ursol, Grigoriy; Sobchenkо, Dmytro; Boichenko, Hlib (Collection of scientific papers «ΛΌГOΣ», 2025)
Surgical site infections (SSI) are one of the most common postoperative complications, significantly impacting surgical outcomes, the duration of hospitalization, healthcare system costs, and patients' quality of life [1, 7, 8]. SSI is the third most frequent category of hospital-acquired infections